2010
DOI: 10.1111/j.1749-4877.2010.00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing crop damage caused by house mice (Mus domesticus) in Australia

Abstract: A large-scale outbreak of the house mouse populations occurs in grain growing in Australia on average once every four years. High densities of mice cause major yield losses to cereal crops, and low to moderate densities of mice also cause some losses. Several predictive models based on rainfall patterns have been developed to forecast mouse density. These models carry some uncertainty and the economic value of basing management actions on these models is not clear. Baiting is the most commonly used method and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Rodents are among the most important vertebrate pests in many parts of the world, causing economic, social, and environmental costs and damage [ 1 , 2 ]. Mice, in particular, are considered serious agronomic pests both in the preharvest and postharvest stages [ 3 , 4 ]. Moreover, they can endanger public health by spreading diseases to humans [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rodents are among the most important vertebrate pests in many parts of the world, causing economic, social, and environmental costs and damage [ 1 , 2 ]. Mice, in particular, are considered serious agronomic pests both in the preharvest and postharvest stages [ 3 , 4 ]. Moreover, they can endanger public health by spreading diseases to humans [ 1 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rodent’s populations can rapidly grow, resulting in extensive damage to electrical installations, properties, food stores, crops, and grains. The World Health Organization reported that 5-22% of the total global food production is lost by rodent activities [ 34 ]. Anthropogenic activities contribute to ecosystem modifications with subsequent changes in the ecological distribution and prevalence of rodents [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, rabbits breed all year round; they are grazers, preferring to eat the green leaves of crops rather than seeds. For this reason, an experimental design used for studying house mouse damage to crops (Kaboodvandpour and Leung, 2010) could be used in a rabbit-damage study.…”
Section: Burrowmentioning
confidence: 99%